Osculating paraboloid - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2005)
Osculating paraboloid of second order have been studied in classical differential geometry. In this article we generalize this concept to osculating paraboloids of higher order. This yields a visualization of the local properties of a given surface which depend on the derivatives of higher order.